锥齿轮-斜齿轮减速机的轴向力分析 - 王明松 (Jixie chuandong)
The size and direction of the axial force of helical-spiral bevel gear reducer under several conditions of different rotation and direction is analyzed.The optimization of the rotation direction combination of spiral bevel gears is carried out,the superposition problem of the axial force is avoided,and the force of the gear shaft and box is improved,the lifetime of bearings and reducer is increased.